Varietal Discrimination of Pineapple (Ananas comosus L.) Using Chromatographic Fingerprints and Chemometrics - Almie Amira Munaras Khan; Norashikin Saim; Rossuriati Dol Hamid; Rozita Osman; Siti Raihan Zakaria (Indonesian Journal of Chemistry, 2020)
Online solid-phase extraction-liquid chromatography (online SPE-LC) with diode array detector (DAD) was used to obtain the chromatographic fingerprint of bioactive compounds of pineapple (Ananas comosus L.). The extracts from 40 samples of three different varieties of pineapple (Morris, MD2, and Josaphine) were obtained using pressurized liquid extraction (PLE) prior to separation using online SPE-LC. The SPE-LC method was optimized and validated and applied to 40 pineapple samples of those three varieties. Seven bioactive compounds identified include catechin, epicatechin, chlorogenic acid, ferulic acid, quercetin, myricetin, and bromelain. For varietal discrimination, the relative areas of 16 selected peaks were subjected to chemometric techniques. The three pineapple varieties were successfully discriminated using cluster analysis (CA) and principal component analysis (PCA).